Pedagogo na cultura digital: contribuição do design educacional para a práxis da polidocência no contexto híbrido - Sanches, Leticia Rocha Justino (2018)
This dissertation is inserted in the research line of teacher training for interdisciplinarity. It has as main objectives to raise the characteristics of the initial formation of the contemporary pedagogue, as well as to understand its relations with the digital culture, proposing, based on documentary and bibliographical analysis, the incorporation of knowledge related to the area of educational design and polydocence in the process of training. The research intends to contribute to the praxis of the pedagogue in the contemporaneity facing the digital culture and the constant technological changes. The methodology adopted by the researcher is qualitative, as it seeks to explain the reasons for the data analyzed in documents. In light of the theories, we chose the contributions of Bernadette Gatti and José Carlos Libâneo, regarding the analysis of the initial formation of pedagogues; Pierre Levy, Manuel Castells and Ángel L. Pérez Gomez, in the approach to digital culture; Andréa Filatro and Vani Moreira Kenski, in the conceptualization of educational design; Daniel Mill, in presenting the concept of polydocence; José Moran in the analysis about hybrid education; and Maurice Tardif, in the presentation of the teaching knowledge. Thus, in this research, we describe the institutionalization of the pedagogy course in the Brazilian higher education system, pointing to the formation dissociated from the digital culture; historically, the trajectory of instructional design to educational design, at national and international level, pointing out its professional specificities; and show the competences of educational design, in interlocution with the concept of polidocencia, for the formation of the pedagogue to act in hybrid spaces as manager of polidocentes teams.In the final part of this research, it is proposed the categorization of some knowledge necessary for the pedagogue to work in the hybrid school space.